Performance-Based Human Resource Management and Federal Employee's Motivation: Moderating Roles of Goal-Clarifying Intervention, Appraisal Fairness, and Feedback Satisfaction. (September 2019) - Lee, Hyung-Woo
Although performance-based human resource management (PHRM) is commonly accepted as a norm in public organizations, many have questioned its motivational effect. Scholars have claimed that the effectiveness of PHRM depends on a number of contingencies and that managers need to consider these contingencies when implementing it. However, little research has provided empirical evidence for such assertions. In this context, this study examines how the qualities of the implementation process moderate the effect of PHRM on intrinsic motivation and work effort. Analyzing the data from the 2014 Federal Employee Viewpoint Survey (FEVS), this study found that the motivational effect was greater for those who perceive performance appraisal as fair and are satisfied with post-assessment feedback. It was somewhat counterintuitive to find that the motivational effect was lessened when managers take active roles to communicate the goals and priorities of the organization and constantly review their employees' progress toward meeting those goals. These results provide the workable leverages for enhancing employee motivation through PHRM. In addition, the main effect of PHRM on work effort was found to be negatively significant, while its effect on intrinsic motivation was positively significant. These unexpected findings account for the multifaceted effects of PHRM.